2019
DOI: 10.1186/s12902-019-0433-9
|View full text |Cite
|
Sign up to set email alerts
|

A pitfall of bilateral inferior petrosal sinus sampling in cyclic Cushing’s syndrome

Abstract: BackgroundClinical care of patients with cyclic Cushing’s syndrome (CS) is challenging. Classical pitfalls include incorrect subtyping, unnecessary surgical procedures and delayed definite treatment.Case presentationA 43-year-old female suffered from a rapidly cycling ectopic CS. She experienced six cycles of severe hypercortisolism within a 2 year period (maximum plasma cortisol 5316 nmol/L, normal range 124.2–662.4 nmol/L; maximum urinary free cortisol 79,469 nmol/24 h, normal range < 414 nmol/24 h) lasting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
(30 reference statements)
0
11
0
2
Order By: Relevance
“…In contrast, false positive results are problematic precisely because patients may end up undergoing unnecessary surgery. One of the possible causes of false-positive and false-negative results is cyclic Cushing's syndrome (CS) [17,18]. Meinardi et al assessed the causes underlying cyclic CS and reported that 54% of the cases were caused by ACTH-producing pituitary adenomas, 26% by ectopic ACTH production, and 11% due to ACTH-independent causes [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, false positive results are problematic precisely because patients may end up undergoing unnecessary surgery. One of the possible causes of false-positive and false-negative results is cyclic Cushing's syndrome (CS) [17,18]. Meinardi et al assessed the causes underlying cyclic CS and reported that 54% of the cases were caused by ACTH-producing pituitary adenomas, 26% by ectopic ACTH production, and 11% due to ACTH-independent causes [19].…”
Section: Discussionmentioning
confidence: 99%
“…For cyclic ACTH-producing pituitary adenomas, IPSS performed during a trough phase can theoretically lead to false-negative results given the lack of a gradient at baseline and after CRH administration [17]. In contrast, IPSS performed during a trough phase of cyclic ectopic ACTH-producing tumors may lead to false positive results [18]. An ectopic tumor that cyclically secretes ACTH could partially suppress the secretory activity of normal corticotrophic cells, resulting in the persistence of the IPS/P ratio, which could consequently raise the IPS/P ratio above the threshold upon CRH stimulation [18].…”
Section: Discussionmentioning
confidence: 99%
“…If intermittent hypercortisolemia is suspected, the procedure should be performed during active phase of the disease. Otherwise, the results might come back negative with the patient unnecessarily exposed to an invasive procedure ( 1 , 19 ).…”
Section: Distinct Features In Diagnostics Of Cyclic Hypercortisolemiamentioning
confidence: 99%
“…Cyclic Cushing's syndrome (also known as intermittent or periodic) is a disease characterized by periods of transient hypercortisolemia shifting into periods of normo-and/or hypocortisolemia. Just as classic Cushing's syndrome, cyclic hypercortisolemia may arise from hormonal activity of corticotropinoma (approximately 80% of all cases), ectopic adrenocorticotropic hormone (ACTH; corticotropin) release, or ACTH-independent causes (1)(2)(3)(4)(5)(6)(7)(8)(9). Retrospective analysis of 201 patients with Cushing's syndrome showed that 15% of them met the diagnostic criteria of intermittent hypercortisolemia and up to 70% showed evidence of cyclicity before the diagnosis (10).…”
Section: Introductionmentioning
confidence: 99%
“…Misdiagnosis may also be a pitfall since CD diagnosis is very challenging. Cortisol levels alternating between periods of hypercortisolism and spontaneous remission as seen in cyclic Cushing's syndrome impede the proper diagnosis [32][33][34]. Several conditions, such as depression, chronic alcohol consume, polycystic ovary syndrome (PCOS) and obesity may muddle the diagnosis leading to activation of the hypothalamus-pituitary-adrenal axis [35].…”
Section: When Surgery Fails and How To Predict Itmentioning
confidence: 99%